STRATEGI MARKETING UNTUK MENINGKATKAN DAYA SAING UMKM KERIPIK MAMAH ESIH DAN GULA AREN ABAH EMPIN DI DESA RIDOGALIH - rizky, anisa; Diah Latipah; Maisya Fatinah Azahra; Neng Nurhayati; Sri Wahyuni; Erry Mulyana; Elangga Prama Raligia Nurfallah (Universitas Nusa Putra & Persatuan Insinyur Indonesia, 2025)
The village of Ridogalih is located in the district of Cikakak, Sukabumi district, West Java Province. The village has an area of about 1,318,47 hectares and a population of about 6,308 people.The majority of its inhabitants are farmers, peasant workers, and entrepreneurs, while the rest are private workers, PNS, and fishermen. The village of Ridogalih is famous for its natural beauty and a variety of tourist possibilities including natural and cultural tours. Tourist attractions in this village include megalithic ruins such as Salak Plain, Curug Chiranji and Banana Hill. The village also has local products like sugar aren, cranberry oil, and peas grinding. Facilities available in Ridogalih Village include five primary schools and one primary secondary school, but there are no secondary schools. The village also has a village health centre (POSKESDES) that serves public health needs.Despite having a lot of potential, the village of Ridogalih is still minimal tourist promotion. Further efforts to promote the village through social media are expected to increase tourist visits and support local economic development